2020
DOI: 10.1080/03043797.2020.1781062
|View full text |Cite
|
Sign up to set email alerts
|

Exploring professional roles for early career engineers: a systematic literature review

Abstract: Nowadays, employees have to take a more flexible and proactive approach to their working lives, involving the continuous management of their own employability, to meet the challenges of a global economy characterised by rapid change (Tomlinson 2007). Higher education institutions increasingly acknowledge their responsibility to guide students, both in their academic growth and in their career development (Burke et al. 2017; National Academy of Engineering 2018).Consequently, the educational field is challenged… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 49 publications
0
22
0
Order By: Relevance
“…An extensive literature review made by Craps et al (2020) showed a huge diversity of possible professional roles frameworks, depending on the goals and the context. Since the PREFER project was in need of a flexible and validated professional roles framework that focuses on young engineers (max 3 years after graduation), transcending the disciplines, we further developed the model suggested by Hofland et al (2015) as it showed high similarities with the model of Spinks et al (2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An extensive literature review made by Craps et al (2020) showed a huge diversity of possible professional roles frameworks, depending on the goals and the context. Since the PREFER project was in need of a flexible and validated professional roles framework that focuses on young engineers (max 3 years after graduation), transcending the disciplines, we further developed the model suggested by Hofland et al (2015) as it showed high similarities with the model of Spinks et al (2007).…”
Section: Discussionmentioning
confidence: 99%
“…This allowed us to develop the PREFER model. However, in an attempt to identify distinguishing competencies, we were hindered by the inconsistency of methods and a lack of well-defined competencies (Craps et. al.…”
Section: Professional Roles Framework For Future Engineersmentioning
confidence: 99%
“…In a systematic literature review, Craps and colleagues found similarities between the models of Hofland et al, Kamp and Klaassen, and Spinks et al, identifying engineers focusing on innovation, optimisation, and customisation. 11,[26][27][28] Kamp and Klaassen described a fourth role, the contextual engineer, emphasising the diversity and different cultures or contexts. However, Spinks et al suggested incorporating future-oriented aspects due to globalisation and rapid change within all roles.…”
Section: Prefer Professional Roles Framework (Prefer)mentioning
confidence: 99%
“…13 Based on the results of these two papers and encouraged by industry, the central focus of the European Erasmus+ Knowledge Alliance PREFER project (Professional Roles and Employability of Future EngineeRs) was defined: the validation of a framework of professional roles for engineers and the implementation of dedicated tests and skills education in engineering curricula to train students for those roles. 14 In this project, the professional roles model is further optimized and validated in close collaboration with industry and the Engineering professional bodies in the three partner countries of this project: Belgium, Ireland, and the Netherlands. 15,16 As part of that, based on mixed methods research at KU Leuven, detailed key competencies were identified for the three different roles.…”
Section: Introductionmentioning
confidence: 99%
“…Collaborative approaches have tended to be ad-hoc, temporary and focused on shortterm gains within the current academic year or recruitment cycle making it difficult to establish sustainable relationships (Vick & Robertson, 2018). Communication can also be challenging as the same terminology is used by GRs and UCAs inconsistently (Craps et al, 2021). This has often led to universities and organisations attempting to 'do their own thing' despite sharing broadly the same objectives of securing employment for their graduates and securing early careers talent for their organisation, respectively (Donald et al, 2021).…”
Section: Introductionmentioning
confidence: 99%